Higher risk of auto versus pedestrian crashes in school-age children on school days. Issue 1 (19th July 2022) - Morrison, Chad; Olson, Ty; McNickle, Allison G.; Fraser, Douglas R.; Kuhls, Deborah A.; Gryder-Culver, Laura K.; Slinkard-Barnum, Samantha; Saquib, Syed F.; Carroll, Joseph T.; Chestovich, Paul J.
Abstract : A review of pediatric auto-pedestrian collisions (APC) found increased frequency of APC in school-age children on school days at times before and after school. The greatest increase was in ages 10-13. Abstract : BACKGROUND: This study examines the rates of pediatric auto versus pedestrian collision (APCs) and determined ages and periods of greatest risk. We hypothesized that the rate of APC in children would be higher on school days and in the timeframes correlating with travel to and from school. METHODS: Retrospective case-control study of APC on school and nonschool days for patients younger than 18 years at an urban Level II pediatric trauma center from January 2011 to November 2019. Frequency of APC by hour of the day was plotted overall, for school versus nonschool days and for age groups: 0 year to 4 years, 5 years to 9 years, 10 years to 13 years, and 14 years to 17 years. t Test was used with a p value less than 0.05, which was considered significant. RESULTS: There were 441 pediatric APC in the study period. Frequency of all APC was greater on school days (0.174 vs. 0.101; relative risk [RR], 1.72, p < 0.001), and APC with Injury Severity Score greater than 15 (0.039 vs. 0.024; p = 0.014; RR, 1.67; 95% confidence interval, 1.10–2.56). Comparing school day with nonschool day, the 0-year to 4-year group had no significant difference in APC frequency (0.021 vs. 0.014; p = 0.129), APC frequency was higher on school days in all other age groups: 5 years to 9 years (0.036 vs. 0.019; RR, 1.89; p = 0.0134), 10 years to 13 years (0.055 vs. 0.024; RR, 2.29; p < 0.001), and 14 years to 17 years (0.061 vs. 0.044; RR, 1.39; p = 0.045). The greatest increase in APC on school days was in the 10-year to 13-year age group. DISCUSSION: All school age children are at higher risk of APC on school days. The data support our hypothesis that children are at higher risk of APC during transit to and from school. The age 10-year to 13-year group had a 129% increase in APC frequency on school days. This age group should be a focus of injury prevention efforts. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level IV. Abstract :